FENOMENA KAWIN KONTRAK DI KAWASAN PUNCAK BOGOR - Maripah, Siti Sarah (Universitas Pendidikan Indonesia, 2016)
Marriage is a bond which is carried by a pair of human who love each other. Marriage was also accompanied by good purpose and must be complete certain requirements in order to be legally in law and religion. In fact, occurredÂ a phenomenon that makes the practice of marriage as deviant behavior. The phenomenon is a marriage between Middle Eastern Tourist with a local woman accompanied agreements specified period or so-called marriage contract in Puncak Bogor West Java. This research will describe an explain the phenomenon of marriage contract from the standpoint of social deviation. This research used a qualitative approach and descriptive study method. These research and method are used to obtain the conclusion from some information and data acquired about phenomenon of marriage contract. Data collection techniques in this research use indepth interviews, observasion, and documentation. Based on the result of research on the perpetratos of marriage contract and village community,Â middle eastern tourist arranged marriage contract to get the biological needs, and a local woman arranged a marriage contract to suficient the economic needs. This marriage contract have so many impact on various aspects of economic, social cultural and psychological for women. Marriage contract belongs to the social deviation, because the implementation is not accordance with religion dan law. This phenomenon still continues until now, but it is more closed. Marriage contract occurred with the support by the local tourism movers are involved in the process of the marriage contract.